Utility of Hepatic Transporters as Multimodal Gene Reporters for Cell‐Based Medicine. Issue 12 (8th October 2020) - Padhiar, Arshad Ahmed; Faqeer, Abdullah; Sun, Shimin; Hamid, Md Rana; Liao, Jinqi; Zhou, Yan; Ahmmed, Bulbul; Qin, Xialing; Changjun, Tie; Gao, Shuping; Yu, Shan; Song, Ming; et al.
Abstract: Hepatic transporters facilitate the uptake of xenobiotic compounds and confer immense potential as multimodality reporters, as they can uptake multitude of bioluminescent, fluorescence, near Infra‐red (NIR), and magnetic resonance imaging (MRI) compounds. Here, it is aimed to identify the prospects of three human hepatocyte membrane proteins, organic anion transporters (OATP) 1B1, OATP1B3, and sodium‐taurocholate cotransporting polypeptide in tracing the transplanted cells dynamics, by the uptake of clinically approved MRI compound, gadolinium ethoxybenzyl‐diethylenetriaminepentaacetic acid (GD‐EOB DTPA) or NIR fluorescent dye, Indocyanine Green (ICG). First, OATP1B1 is introduced as new MRI reporter which is the human orthologue of previously established rodent (Oatp1a1) reporter. Comparative sequential assays by assimilating MR image parameters reveal OATP1B3 as superior reporter on T1‐weighted images and display highest contrast enhancement reported to‐date when using a clinical 3T MR scanner (≈21‐fold in vitro; ≈8‐fold in vivo). Stably expressing these hepatic transporters have no effect on human adipose derived mesenchymal stem cells (hADSCs) characteristics. However, only OATP1B3 able to trace as few as 2 × 10 5 hADSCs intramuscular xenograft survival time on NIR and 3T MRI. These data suggest that OATP1B3 is relatively a robust Gd‐EOB‐DTPA/ICG‐dependent multimodality reporter in visualizing dynamic processes for cell‐based therapies. Abstract : Clinical imaging is indispensable for measuring the safety and efficacy of cell‐based therapy. However, the ability to trace long‐term fate of transplanted cells with current technologies is limited. This article demonstrates human hepatocyte transporters as multimodal gene reporters, as these transporters can specifically uptake variety of clinically approved fluorescent, bioluminescent, and magnetic resonance imaging compounds.